A self-amplifying RNA vaccine provides protection in a murine model of bubonic plague - Shattock, Robin John; Andrianaivoarimanana, Voahangy; McKay, Paul F.; Randriantseheno, Lovasoa Nomena; Murugaiah, Valarmathy; Samnuan, K.; Rogers, Paul; Tregoning, John S.; Rajerison, Minoarisoa; Moore, Kristoffer M.; Laws, Thomas Robert; Williamson, E. Diane (Frontiers in Microbiology, 2023)
Mice were immunized with a combination of self-amplifying (sa) RNA constructs for the F1 and V antigens of Yersinia pestis at a dose level of 1 μg or 5 μg or with the respective protein sub-units as a reference vaccine. The immunization of outbred OF1 mice on day 0 and day 28 with the lowest dose used (1 μg) of each of the saRNA constructs in lipid nanoparticles protected 5/7 mice against subsequent sub-cutaneous challenge on day 56 with 180 cfu (2.8 MLD) of a 2021 clinical isolate of Y. pestis termed 10-21/S whilst 5/7 mice were protected against 1800cfu (28MLD) of the same bacteria on day 56. By comparison, only 1/8 or 1/7 negative control mice immunized with 10 μg of irrelevant haemagglutin RNA in lipid nanoparticles (LNP) survived the challenge with 2.8 MLD or 28 MLD Y. pestis 10-21/S, respectively. BALB/c mice were also immunized with the same saRNA constructs and responded with the secretion of specific IgG to F1 and V, neutralizing antibodies for the V antigen and developed a recall response to both F1 and V. These data represent the first report of an RNA vaccine approach using self-amplifying technology and encoding both of the essential virulence antigens, providing efficacy against Y. pestis. This saRNA vaccine for plague has the potential for further development, particularly since its amplifying nature can induce immunity with less boosting. It is also amenable to rapid manufacture with simpler downstream processing than protein sub-units, enabling rapid deployment and surge manufacture during disease outbreaks.